2007
DOI: 10.1029/2006jd008295
|View full text |Cite
|
Sign up to set email alerts
|

A Lagrangian perspective of the tropopause and the ventilation of the lowermost stratosphere

Abstract: Back trajectories driven by large‐scale analyzed wind fields are used to investigate troposphere to stratosphere transport (TST) in the Northern Hemisphere tropopause region, as well as the surface sources for such transport, defined in terms of the locations where each trajectory last left the atmospheric boundary layer (log pressure height z* < 1 km). The proportion χBL of those trajectories arriving in the tropopause region that have visited the boundary layer within the previous fixed time period (typicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
109
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(127 citation statements)
references
References 55 publications
17
109
1
Order By: Relevance
“…similar results from the trajectory studies by Berthet et al (2007); Hoor et al (2010) and the O 3 -N 2 O correlation analysis by Hegglin and Shepherd (2007)). Furthermore, they used simultaneous measurements of SF 6 and CO 2 to calculate tracer transit times (resulting from residual circulation transport and two-way mixing) from the tropical upper troposphere to the extratropical LMS.…”
supporting
confidence: 72%
“…similar results from the trajectory studies by Berthet et al (2007); Hoor et al (2010) and the O 3 -N 2 O correlation analysis by Hegglin and Shepherd (2007)). Furthermore, they used simultaneous measurements of SF 6 and CO 2 to calculate tracer transit times (resulting from residual circulation transport and two-way mixing) from the tropical upper troposphere to the extratropical LMS.…”
supporting
confidence: 72%
“…In addition, some studies have identified the longitudinal distribution of the STE activity [e.g., Postel and Hitchman, 1999;Sprenger et al, 2007]. It is possible that the spatial variation in the stratospheretroposphere exchange which our study and the others have identified is mainly related to Asian monsoon and cyclonic activity [e.g., Chen, 1995;Dethof et al, 1999;Sprenger and Wernli, 2003;Park et al, 2007;Levine et al, 2007;Berthet et al, 2007].…”
Section: Deduced Transport Pathways To the Lower Stratospherementioning
confidence: 99%
“…Hatsushika and Yamazaki, 2003;Bonazzola and Haynes, 2004;Fueglistaler et al, 2004 and, usually in an effort to explain the very low water vapour mixing ratios observed in the tropical lower stratosphere (see e.g., Mote et al, 1995 and. There have been relatively few model studies of transport from the TTL into the ELS (Chen, 1995;Berthet et al, 2007) despite recognition of its potential importance (e.g. Allam and Tuck, 1984;Holton et al, 1995) and observational evidence of its effects on the chemical composition of the mid-latitude lower stratosphere (e.g.…”
Section: Introductionmentioning
confidence: 99%